The Intersection of Literature and Da'wah: Reflections of The Third-World Muslim Society in V.S. Naipaul's Beyond Belief Islamic Excursions Among The Converted Peoples - Nurholis, Nurholis; Asy Syamil, Muhammad Fikri (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
This study examines the communities in four countries—Indonesia, Iran, Pakistan, and Malaysia in Beyond Belief: Islamic Excursions Among the Converted Peoples, which portrays Muslim Through the character of "I," who evolves into an authoritative narrator, Naipaul seeks to justify the representations in the narrative as reflections of his own perspective. Despite the often negative depictions of Muslim societies in these countries, Naipaul aims to document aspects of the Muslim community that have remained unrecorded. His efforts to make Islam 'readable' are evident throughout the work, yet they evoke a sense of powerlessness among those subjected to such portrayals, who are unable to voice their own narratives. From a da’wah studies perspective, the implications of this research lie in critically assessing external narratives that marginalize Muslim voices. By deconstructing these representations, this study highlights the importance of reclaiming an authentic Islamic identity and countering misrepresentations. Furthermore, it invites reflection on how da’wah can respond to external narratives, promoting a more accurate and fair understanding of Islam in a fragmented global society.